High levels of neurological involvement but low mortality in miliary tuberculosis: a 6-year case-series from the UK. Issue 5 (4th February 2016) - Venkatraman, Navin; King, Thomas; Bell, David; Woltmann, Gerrit; Wiselka, Martin; Abubakar, Ibrahim; Pareek, Manish
Tuberculosis (TB) remains one of the biggest global health challenges. Whilst the greatest burden of active disease is seen in Asia and Africa [1], TB remains a significant issue in the UK. Miliary TB is one of the severest manifestations of TB disease [2–4]. Up-to-date clinicopathological data on miliary TB from the developed world are lacking. We undertook a comprehensive 6-year review (2007–2012) of cases presenting to a single UK centre with an ethnically diverse population with high levels of population exchange with the Indian Subcontinent and Africa. Miliary TB was defined as the presence of miliary nodules on thoracic imaging in patients who presented with symptoms compatible with the diagnosis and either culture of Mycobacterium tuberculosis complex or culture-negative patients with clinical and/or histological features compatible with TB who were commenced on a course of antituberculous therapy (ATT). Miliary TB: high level of CNS involvement best investigated by head MRI which suggests re-evaluation of NICE guidance http://ow.ly/X3CDK